Dynamics of Urban Heat Island and NO2 Gas During the Covid-19 Pandemic - Risnayah, Siti; Mudhalifana, Waode Sitti; Restele, La Ode (Tunas Geografi, 2023)
To know the COVID-19 pandemic™s impact on the environment, an analysis of Urban Heat Island and pollutant gas was carried out. From March to June 2020, the Indonesian government implemented the Large-Scale Social Restrictions (PSBB) policy, requiring people to limit activities in public places. The data used are Land Surface Temperature (LST) from the Terra MODIS and Nitrogen Dioxide (NO2) concentration from the TROPOMI sensor. The data is processed using the Google Earth Engine to produce comparative values before the PSBB implementation (2019), during (2020), and after (2021-2022). The LST will be derived into Surface Urban Heat Island (SUHI) to compare climate conditions in urban (Kendari) and rural areas (Ranomeeto, Lalonggasumeeto, North Moramo). The results show that reducing community activities during the pandemic was not able to reduce LST but succeeded in inhibiting the increase rate. The LST trend is more affected by rainfall variables where higher rainfall causes lower LST and vice versa. The SUHI value shows a downward trend, meaning that the Urban Heat Island effect has been inhibited. The most significant impact of PSBB was a 25.9% reduction in NO2 concentration. These results prove that the COVID-19 pandemic has successfully restored environmental health constantly exposed to air pollution. Keywords: COVID-19, Urban Heat Island, NO2, PSBB, Land Surface Temperature